What Makes a Good Human Smuggler? The Differences between Satisfaction with and Recommendation of Coyotes on the U.S.-Mexico Border. Issue 1 (March 2018) - Slack, Jeremy; Martínez, Daniel E.
This article draws on a unique dataset of more than eleven hundred postdeportation surveys to examine migrants' experiences with coyotes (human smugglers) along the U.S.-Mexico border. Our focus is on migrants' satisfaction with the services provided by their most recent smuggler and whether they would be willing to put family or friends in contact with that person. We find a distinct difference between people's expectations for their own migratory experience compared to what they would be willing to subject loved ones to. Expectations of comfort and safety are decidedly low for oneself; but for loved ones, a more expressive, qualitative assessment shapes their willingness to recommend a coyote: qualities such as trustworthiness, honesty, comportment, and treatment come to the fore. News coverage focusing on the deaths of smuggled migrants often portrays coyotes as nefarious and exploitative, but the migrant-smuggler relationship is much more complex than suggested by these media accounts. We provide empirical insight into the factors associated with successful, satisfactory, and safe relationships between migrants and their guides.